THE INFLUENECE OF CUSTOMER RELATIONSHIP MANAGEMENT TO THE CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION - -, Ariyanda Putra Rusari B12111033 (Jurnal Manajemen Update, 2019)
The purpose of this study is to analyze how the influence of customers relationship management (CRM) to customer loyalty through customer satisfaction. This research using quantitative approach. The sample in this study is 100 airline users who have used Citilink airline by using purposive sampling method and purposive technique. The instrument of this study using questionnaires and analyzed using path analysis. The results in this study show that CRM has an insignificant influence on customer loyalty Improved customer loyalty 25.7%, and 74.3% restitution. Can be said the effect of Customer Relationship Management on Customer Loyalty through Customer Satisfaction is very small.Keywords: Customer Relationship Management, Customer Loyalty, customer satisfaction, PT.CitilinkBibliographyAprillita, Lusia. 2011. Pengaruh CRM tehadap Loyalitas pada PT. Bank Negara Indonesia (BNI) Tbk, Kantor Cabang UI Depok. Depok: Universitas Indonesia.Arif Gifano 2011. Pengaruh Customer Relationship Management Terhadap Loyalitas Pelanggan pada maskapai Garuda Indonesia; Universitas IndonesiaBaker, S. 2003. New Consumer Marketing: Managing a Living Demand System. England: WileyBowen, J. T. & Chen, S. L. 2001. The Relationship Between Customer Loyalty and Customer Satisfaction, International Journal of Contemporary Hospitality Management. 1(2): 213â€“217.Dharmmesta, Basu Swastha. 1999. Loyalitas Pelanggan: Sebuah Kajian Konseptual sebagai Â Â Â Panduan bagi Peneliti. Jurnal Ekonomi dan Bisnis Indonesia Vol . 14.Duygu Kocoglu Sevcan Kirmaci (2012), â€œCustomer Relationship Management And Customer Loyalty; A Survey In The Sector Of Bankingâ€Garima Malik (2015), â€œImpact of Customer Relationship Management on Customer Loyalty and Customer Retention with reference to Automobile Sectorâ€Griffin, Jill. 2005. Customer Loyalty: How to Earn It, How to Keep It. Alih Bahasa: Dr. Dwi Kartini Yahya. Jakarta: Erlangga.Hair, Joseph F., Robert P. Bush, & David J. Ortinau. 2006. Marketing Research: Within a Changing Information Environment. 3rd Edition. McGraw-Hill.Keegan, Warren J., Sandra Ernst Moriarty, & Thomas R. Duncan. 1995. Marketing. 2nd Edition. New Jersey: Prentice Hall.Kincaid, Judith W. 2003. Customer Relationship Management: Getting It Right. New Jersey: Prentice Hall.Kottler, P. a. (2014). Marketing Management (Vols. Fourteenth Edition,). USA: Prentice Hall Publishing.Kotler, Philip. 1997. Manajemen Pemasaran: Analisis, Perencanaan, Implementasi, an Kontrol. Jilid 1. Edisi Revisi.Lin, Cho-Pu, Yann-Haur Huang, Chien-Ting Chen, & Hsing-Yun Chang. 2009. CRM Implementation Strategy in Taiwanâ€™s Banking IndustryLukas, Ade Paul. 2001. Customer and Partner Relationship Management. Jakarta Telematic Research Group.Malhotra, Naresh K. 2004. Review of Marketing Research, Vol. 1. North Castle: M.E. Sharpe.Oliver, Richard L. 1993. A Conceptual Model of Service Quality and Service Satisfaction: Compatible Goal, Different Concept. Journal Advances in Services Marketing and Management, Vol. 2.Rana Saifullah Hassana, Aneeb Nawazb, Maryam Nawaz Lashari C, Dr. Fareeha Zafard (2014) â€œEffect of Customer Relationship Management on Customer Satisfactionâ€, Prague, Czech RepublicSivadass, E. & Baker-Prewitt, J. L. 2000. An Examination of the Relationship Between Service Quality, Customer Satisfaction, and Store Loyalty, International Journal of Retail & Distribution Management. 28(2): 73â€“82.Prasetyo, Bambang, & Miftahul Jannah. 2005. Metode Penelitian Kuantitatif: Teori dan Aplikasi. Jakarta: PT. Raja Grafindo Persada.Timm, Paul R. 2001. Seven Power Strategies for Building Customer Loyalty. USA: Amacom.Yim, Frederick Hong-Kit, Rolph E. Anderson, & Srinivasan Swaminathan. 2004. Customer Relationship Management: Its Dimensions and Effect on Customer Outcomes.Zeithaml, Valarie A., Roland T. Rust, & Katherine N. Lemon. 2000. Driving Customer Equity: How Customer Lifetime Value Is Reshaping Corporate Strategy. USA: Amazon.com, Inc.Other Sourceen.Wikipedia. (2015, January 7). Convergent Validity. Retrieved July 22, 2016, from Wikipedia: https://en.wikipedia.org/wiki/Convergent_validityThe Boeing Company, Current Market Outlook, 2003, 2009, & 2010. http://marketing-teori.blogspot.comhttp://marketing-teori.blogspot.comData Statistik Direktorat Transportasi Udarahttp://economicsjurnal.blogspot.comhttps://www.citilink.co.id/en/company-profile